Apocynum venetum leaf extract, an antihypertensive herb, inhibits rat aortic contraction induced by Angiotensin II: a nitric oxide and superoxide connection - Lau, Y.S.; Kwan, C.Y.; Ku, T.C.; Hsieh, W.T.; Wang, H.D.; Nishibe, S.; Dharmani, M.; Mustafa, Mohd Rais (2012)
Ethnopharmacological relevance: The leaves extract of Apocynum venetum (AVLE), also known as luobuma, have long been used in traditional Chinese medicine to treat hypertension and depression in parts of China and it has been shown to possess anti-oxidant and anti-lipid peroxidation effects. AVLE (10 Î¼g/ml) has been reported to have a long-lasting endothelium-dependent relaxant effect and this effect has been proposed to be due to its nitric oxide(NO)-releasing and superoxide anion(SOA)-scavenging properties. Aim of the study: The present study seeks to evaluate the differential actions of AVLE extract between Ang II- and PE-induced vasoconstriction and the involvement of superoxide anions. Materials and methods: Single dose of Ang II (100 nM and 1 nM)- or PE (0.1 Î¼M)-induced contraction were assessed in both endothelium-intact and -denuded aortic rings after pre-incubation of AVLE (10 Î¼g/ml) for 15 min. The experiment was repeated in either the presence of NO synthase inhibitor, l-NAME (300 Î¼M) or selective AT1 receptor inhibitor, losartan (0.1 nM), or superoxide scavenger, tiron (1 mM) or a combination of l-NAME and AVLE. Superoxide production was measured by using enhanced-chemiluminescence assay. Results: We have demonstrated that AVLE (10 Î¼g/ml) effectively suppressed the Ang II-induced contraction (100 nM and 1 nM) of both endothelium-intact and -denuded rat aortic rings. In endothelium-intact rings, l-NAME, reversed AVLE-induced inhibition of Ang II-contraction. PE-induced contraction was significantly inhibited by AVLE in endothelium-intact rings, but not in endothelium-denuded rings. The inhibition by AVLE of PE-induced contraction was totally abolished in the presence of l-NAME. Ang II-induced SOA production concentration dependently with the optimal effect seen at 100 nM of Ang II, and AVLE (0.3, 1, 10 Î¼g/ml) reduced this effect. SOA production in Ang II-stimulated rings was significantly higher than unstimulated control rings, while PE did not stimulate SOA production at all. SOA formation in the presence of Ang II was also inhibited in the presence of SOD (superoxide scavenger), DPI (NADPH inhibitor) and losartan (specific AT1 receptor antagonist). Conclusion: These results collectively suggest that the ability of AVLE in inhibiting Ang II-induced contraction via its SOA scavenging properties and nitric oxide releasing effect may account for its usage as an antihypertensive treatment in traditional folk medicine.